Chicken man - Edwards, Michelle (New York : Mulberry Books, 1994)
Each time Chicken Man is moved into a new job on the kibbutz, someone else wants to take that job instead, and the chickens suffer as a consequence.
Keywords: Kibbutzin-Fiction; Occupations-Fiction; Chickens-Fiction; Israel-Fiction; Jews-Israel-Fiction